Adverse events after Tetanus Toxoid, Reduced Diphtheria Toxoid and Acellular Pertussis (Tdap) Vaccine administered to adults 65 years of age and older reported to the Vaccine Adverse Event Reporting System (VAERS), 2005–2010 - Moro, Pedro L.; Yue, Xin; Lewis, Paige; Haber, Penina; Broder, Karen (Vaccine, 2011)
► Tdap vaccine was not licensed in adults ≥65 years due to insufficient safety data. ► We assessed the safety of Tdap vaccine in adults aged ≥65 years in VAERS. ► We searched VAERS for adverse events in adults ≥65 years who received Tdap vaccine. ► No safety concerns that warrant further study were identified. ► These data provides useful baseline information to assist future monitoring efforts. Tetanus toxoid, reduced diphtheria toxoid, and acellular pertussis (Tdap) vaccine was not licensed for use in adults aged ≥65 years due to lack of sufficient efficacy and safety data. To characterize reports to the Vaccine Adverse Event Reporting System (VAERS) among adults aged ≥65 years who received Tdap vaccine ‘off-label’ to assess for potential vaccine safety concerns. We searched VAERS for US reports of adverse events (AEs) in subjects aged ≥65 years who received Tdap vaccine from 9/1/2005 to 9/08/2010. Medical records were requested for all reports coded as serious (death, hospitalization, prolonged hospitalization, permanent disability, life-threatening-illness). Proportional reporting ratio (PRR) was used to assess for higher proportionate reporting for AEs after Tdap compared with Td reports in subjects aged ≥65 years. VAERS received 243 reports following Tdap administered to persons aged ≥65 years. Eleven (4.5%) reports were serious, including two deaths. Most common AEs were local reactions in 100 (41.2%) reports. Seventy-eight (32.1%) reports contained coding terms that denoted inappropriate administration of vaccine. ‘Cough’ was the only term associated with disproportionately higher reporting after Tdap compared with Td. Six of seven Tdap reports containing the term ‘Cough’ were non-serious. Clinical review of serious reports identified no unusual patterns of AEs. Our VAERS review of the ‘off-label’ use of Tdap vaccine in adults ≥65 years did not find any safety concerns that warrant further study. These data will provide useful baseline information to assist CDC and FDA with monitoring efforts as permissive recommendations for Tdap in older persons are adopted.